Fmoc-diphenylalanine self-assembly mechanism induces apparent pKa shifts - Tang, Claire (Langmuir : the ACS journal of surfaces and colloids, 2009)
We report the effect of pH on the self-assembly process of Fmoc-diphenylalanine (Fmoc-FF) into fibrils consisting of antiparallel beta-sheets, and show that it results in two apparent pKa shifts of approximately 6.4 and approximately 2.2 pH units above the theoretical pKa (3.5). Using Fourier transform infrared (FTIR) spectroscopy, transmission electron microscopy (TEM), wide angle X-ray scattering (WAXS), and oscillatory rheology, these two transitions were shown to coincide with significant structural changes. An entangled network of flexible fibrils forming a weak hydrogel dominates at high pH, while nongelling flat rigid ribbons form at intermediate pH values. Overall, this study provides further understanding of the self-assembly mechanism of aromatic short peptide derivatives